PEMANFAATAN AFTER EFFECTS MOTION GRAPHICS UNTUK MEMBANTU STRATEGI KOMUNIKASI PROGRAM INOVASI KASIH JERUK PURUT - Prita Suci Nurcandrani; Rizki Ardhi Rahman; Bumi Bidadari Shaskia (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The Banyumas Regency Health Office summarized that in 2019, stunting in the North Purwokerto Subdistrict area reached 261 cases. In the same time, the infant mortality rate in Banyumas Regency reached 127 cases including four cases were occured in the work area of North Purwokerto II. The Kasih Jeruk Purut Program aims to increase the coverage of exclusive breastfeeding to more than 90% in the work area of the Puskesmas Purwokerto Utara II with the main objective is to reduce infant mortality and prevent stunting. The socialization activities carried out require tools to facilitate effective communication to occur. Communication aids in the form of brochures or leaflets provided by the central government often did not meet the target program effectively because the brochures contained too many written elements. The purpose of this PKM is to help provide effective After Effects Motion Graphics to assist the implementation of the Kasih Jeruk Purut Program. The design of the implementation media design for The Kasih Jeruk Purut Program is in the form of a simple Motion Graphics design containing the content of the right breastfeeding method. After making After Effects Motion Graphic, it was continued with the socialization of this application to the head of the program and the Kasih Jeruk Purut team, and tested it on patients and continued with evaluation.